Anti-inflammatory and analgesic activities of black cumin (BC, Nigella sativa L.) extracts in in vivo model systems - Shaheen, Nazma (2023)
Black cumin (Nigella sativa) is a widely used ingredient of traditional medicine for its broad-spectrum pharmacological actions, including analgesic, bronchial asthma, anti-inflammatory properties, and others. We sought to evaluate BC extracts' efficacy for the anti-inflammatory and analgesic properties using a comprehensive in vivo and in silico experimental setup. To investigate whether BC extract has anti-inflammatory and analgesic therapeutic potentials in vivo anti-inflammatory activity by carrageenan-induced rat paw edema, analgesic activity by acetic acid-induced writhing test and ingenuity analysis of the BC extracts in inflammation control.